The Significance of The Bio-Psycho-Spiritual Dimension in Relation to Islamic Education - Sri Haryanto (Postgraduate, University of Mataram, 2025)
The psychological dimension involves self-control, purification of the psyche, and mental well-being. The intellectual dimension emphasizes knowledge, critical thinking, and decision-making. The emotional dimension focuses on faith and ethics, while the spiritual dimension strengthens the connection with God and spiritual well-being. Islamic education has important relevance in developing human potential as bio-psycho-spiritual beings. Islamic education provides a holistic approach that includes the physical, mental, and spiritual aspects of individuals. Islamic education helps man in understanding the purpose of life, knowing Allah, and developing a deeper relationship with Him. By integrating biological, psychological, and spiritual aspects, Islamic education provides a comprehensive framework for the formation of good character and harmony in human life. This article aims to explain the relevance of the bio-psycho-spiritual dimension of man to Islamic education. This discussion is important to help us understand how Islamic education can contribute to developing a balanced and well-rounded individual.